(untitled) (The Research of Medical Science Review, 2025)
Background: Meningitis is still difficult to diagnose accurately, especially when LP is not possible. CE-FLAIR MRI has been reported to be useful for detecting meningeal inflammation, but its PPV, versus CSF analysis, the gold standard, is to be proven. Objective: To assess the diagnostic performance of CE-FLAIR MRI for meningitisagainst analysis of CSF as the standard. Methods: Between January 2023 and December 2023, this cross-sectional study was carried out at the Armed Forces Institute of Radiology & Imaging (AFIRI), Rawalpindi. Suspected meningitis patients (n=112) had both CE-FLAIR MRI and CSF examination within 48 hours of hospital admission. Leptomeningeal enhancement was evaluated in MRI by two blinded neuroradiologists. Diagnostic performance (PPV, sensitivity, specificity, negative predictive value [NPV], accuracy) was compared with CSF findings (pleocytosis, biochemistry, and microbiology). Results: CE-FLAIR MRI showed a total PPV of 86.2% (95% CI: 81.4–90.1), sensitivity of 86.2% (95% CI: 81.3 90.4), specificity of 90.7% (95% CI: 86.5–94.0), NPV of 90.7% (95% CI: 86.2–94.1), and accuracy of 88.4%. Subgroup analysis was found to have greater PPV for bacterial meningitis (91.4%) than for viral (78.9%) and fungal (75.0%) meningitis. False positives (n=8) were mostly caused by metastatic disease (62.5%), whereas false negatives (n=5) were due to early viral meningitis (60%). Inter-reader agreement was very good (κ=0.82). Conclusion: CE FLAIR MRI is a safe diagnostic tool for meningitis, especially in bacterial cases, and could be an added value when CSF examination is inconclusive or contraindicated. However, clinical correlation is still indispensable to reduce misinterpretation.